Self-cleaning, waterproof and heat-dissipating coating as well as preparation method and application thereof

Through the cross-linking polymerization technology of perfluorinated compounds, a self-cleaning, waterproof, and heat-dissipating coating that can be quickly cured at room temperature is prepared, which solves the deficiencies of existing electronic device coatings in terms of waterproofing, cleaning, and heat-dissipation performance, and achieves Coating effect with high transparency and low slip angle.

CN119331474AActive Publication Date: 2025-01-21QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411454126.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-21
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

Existing electronic device coatings have shortcomings in waterproof, cleaning and heat dissipation performance, making it difficult to meet the needs of high-power density electronic components.

Method used

Using perfluoro-1,2-dimethylcyclohexane and hexafluoropropylene dimer as solvents, through cross-linking polymerization with perfluorodecyl acrylate and isobornyl acrylate, a self-cleaning, waterproof, Heat dissipating paint. The coating can be quickly cured at room temperature and is suitable for coating and packaging of electronic components.

Benefits of technology

It achieves good waterproofing, heat dissipation and self-cleaning properties on the surface of electronic devices, is suitable for coating applications with high transparency and low slip angle, and improves the working efficiency and reliability of electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331474A_ABST
    Figure CN119331474A_ABST
Patent Text Reader

Abstract

The invention discloses a self-cleaning, waterproof and heat-dissipating coating and a preparation method and application thereof.The preparation method of the self-cleaning, waterproof and heat-dissipating coating comprises the following steps that perfluoro 1, 2-dimethylcyclohexane and hexafluoropropylene dimer are evenly mixed at the temperature of 20-35 DEG C; after the reaction is finished, adding perfluorodecyl acrylate into the mixture, and stirring at 20-35 DEG C for a set time; after stirring is completed, AIBN is added into a reaction system, heating is conducted, perfluorodecyl acrylate is subjected to self-crosslinking polymerization for set time, and the coating is obtained. Compared with a traditional sliding coating, the SUSC effectively solves the problem that the self-cleaning performance is reduced due to lubricant loss. The SUSC coating also has a low slip angle (approximately equal to 8 degrees), high transparency, and good heat dissipation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of coatings, and in particular relates to a self-cleaning, waterproof, heat-dissipating coating and a preparation method and application thereof. Background Art

[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.

[0003] With the rapid development of high-performance electronic components, the power density of electronic devices has increased dramatically. Poor waterproof, clean and heat dissipation performance of electronic components usually causes the failure of electronic devices. Functional coatings for high-power density electronic components are essential for the development of next-generation integrated electronic devices. Traditional encapsulation coatings, such as waterproof films and heat sinks, have played an important role in the operation of electronic systems. At present, transparent electronic products including displays, solar cells, smart windows, electronic skin and other wearable medical heating patches have been widely used in modern society. However, there are also many challenges in their application process. For example, high optical transparency and clean surface are essential for solar cells. Because dust accumulation on the surface often leads to low photovoltaic (PV) conversion efficiency and even hot spots, the latter will cause irreversible damage to solar panels. For more complex circuit boards, waterproof and heat dissipation performance is essential. In order to improve the working efficiency of electronic devices under different working conditions, it is necessary to prepare a coating material with good ultra-slip self-cleaning performance, high light transmittance and heat dissipation.

[0004] Lotus-shaped superhydrophobic surfaces with micro / nano rough structures and low surface energy have attracted widespread attention due to their self-cleaning properties. However, low transparency and rough structures hinder their application in the field of electronics. Aizenberg et al. prepared a liquid-injected porous slippery surface (SLIPS) with a large amount of flowing lubricant on its surface and no trapped air. The smooth surface is made by injecting lubricants into rough porous micro / nanostructured substrates (such as metals, glass, plastics, ceramics, wood, fabrics, elastomers, etc.). Others can repel almost all immiscible materials by infiltrating perfluoroalkyl ethers into micro / nanoporous substrates. However, low surface energy perfluoropolyethers or other perfluorinated liquids as lubricants are expensive, toxic and harmful to the environment. In addition, there is a method of preparing porous network microstructures by direct writing in one step using femtosecond lasers, followed by injection of silicone oil to obtain a smooth surface. However, the loss of flowing lubricants on the smooth surface leads to a decrease in sliding ability.

[0005] In order to avoid the use of mobile lubricants, a smooth low-surface-energy wax layer or polymer layer is used to replace the slippery surface. Although lubricant-free slippery surfaces have received much attention, their poor slippery properties, low optical transparency, high thickness, high curing temperature, and poor heat dissipation limit the practical application of slippery surfaces in electronic devices. Therefore, a new coating material is needed to promote the practical application of slippery surfaces in various electronic devices. Summary of the invention

[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a self-cleaning, waterproof, heat-dissipating coating and a preparation method and application thereof.

[0007] In order to achieve the above object, the present invention is implemented through the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a self-cleaning, waterproof, and heat-dissipating coating, comprising the following steps:

[0009] Mix perfluoro-1,2-dimethylcyclohexane and hexafluoropropylene dimer at 20-35°C;

[0010] After the reaction is complete, add perfluorodecyl acrylate and isobornyl acrylate to the mixture and stir at 20-35° C. for a set time;

[0011] After stirring, AIBN is added to the reaction system and heated to allow perfluorodecyl acrylate and isobornyl acrylate to cross-link and polymerize for a set time to obtain a coating.

[0012] The reaction of perfluorodecyl acrylate is as follows:

[0013]

[0014] The inventors found in the experiment that the boiling point of the solvent (such as ethyl acetate, ethanol, etc.) that can be used as isobornyl acrylate is generally high, such as higher than 60°C. After the polymerization of perfluorodecyl acrylate and isobornyl acrylate is completed, the prepared coating is applied to the substrate. The coating is difficult to cure at room temperature and generally needs to be placed in an oven for heating and curing. However, the coating in the present invention is used for spraying on the surface of electronic components. Electronic components are relatively precise and have relatively strict environmental requirements. Too high a drying temperature will destroy the precision of the electronic components and even affect the life of the electronic components.

[0015] After repeated screening of solvents, it was found that when perfluoro 1,2-dimethylcyclohexane and hexafluoropropylene dimer are used as solvents, perfluorodecyl acrylate and isobornyl acrylate can be effectively dissolved. After the cross-linking polymerization of perfluorodecyl acrylate and isobornyl acrylate is completed, the coating can be quickly cured within 60-80s at room temperature after being applied to the substrate, thereby meeting the use requirements of electronic component coatings.

[0016] In addition, when perfluoro 1,2-dimethylcyclohexane and hexafluoropropylene dimer are used as solvents, the coating is applied on the surface of the substrate. During the curing process, perfluoro 1,2-dimethylcyclohexane and hexafluoropropylene dimer will not volatilize, but will be cured as the base material of the coating, forming a coating together with the cross-linked polymerization product of perfluorodecyl acrylate and isobornyl acrylate, and they work together to make the coating have good waterproof, heat dissipation and self-cleaning properties.

[0017] In some embodiments, the mass ratio of perfluoro-1,2-dimethylcyclohexane, hexafluoropropylene dimer, perfluorodecyl acrylate and isobornyl acrylate is 10-15: 4-6: 0.01-0.05: 0.01-0.05.

[0018] Preferably, the mass ratio of perfluoro-1,2-dimethylcyclohexane, hexafluoropropylene dimer and perfluorodecyl acrylate is 10-13: 4-10: 0.02-0.04: 0.02-0.04.

[0019] Preferably, the mass ratio of perfluorodecyl acrylate to AIBN is 2-4:1.

[0020] In some embodiments, the perfluoro-1,2-dimethylcyclohexane and hexafluoropropylene dimer are stirred at 20-35° C. for 20-40 min.

[0021] In some embodiments, after adding perfluorodecyl acrylate and isobornyl acrylate to the mixture, the stirring time is 10-30 minutes.

[0022] In some embodiments, the cross-linking polymerization of perfluorodecyl acrylate and isobornyl acrylate is carried out at a temperature of 55-65° C. and for a time of 1.5-2.5 h.

[0023] In a second aspect, the present invention provides a self-cleaning, waterproof, heat-dissipating coating prepared by the preparation method.

[0024] In a third aspect, the present invention provides the use of the self-cleaning, waterproof and heat-dissipating coating in coating and packaging electronic devices.

[0025] In some embodiments, when coating and packaging an electronic device, the coating is dripped on or applied to the surface of the electronic device and cured at 20-35°C.

[0026] The beneficial effects achieved by one or more embodiments of the present invention are as follows:

[0027] The present invention prepares an electronic device coating SUSC material with good waterproof, heat dissipation and self-cleaning properties by polymerizing perfluorododecyl acrylate monomers. The results show that this multifunctional coating is suitable for coatings in various scenarios. Compared with traditional sliding coatings, SUSC effectively solves the problem of reduced self-cleaning performance due to lubricant loss. The SUSC coating also has a low slip angle (≈8°), high transparency and good heat dissipation (the high transparency is because all the selected raw materials are transparent, and the raw materials do not produce a large amount of hydrogen bonds when cross-linked. The low sliding angle is because the fluorine-containing chain has a low surface energy, and the flexible chain will be arranged upward to form a brush-like structure. The heat dissipation is due to the ultra-thinness (such as up to about 1.5μm) and the polymer cross-linking density is not particularly high). The excellent performance of the SUSC coating makes it a good anti-slip material and is widely used in solar power generation, chip waterproofing and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0029] Figure 1 In the figure, a) is the SEM image of the SUSC coating; b) is the energy dispersive spectroscopy (EDS) of fluorine in SUSC; c) is the cross-sectional SEM image of the coated SUSC; d) and e) AFM images of the SUSC coating on the glass substrate; f) is the FTIR spectrum of PFDA and uncured SUSC; g) is the XPS spectrum of the coated SUSC. Illustration: Schematic diagram of the crystallization of perfluoroalkyl side groups in a highly ordered manner; h) is the XPS element C spectrum of the coated SUSC; i) is the element O peak of the XPS of the coated SUSC;

[0030] Figure 2 In the figure, a) is the UV-VIS-NIR transmission spectra and transparent photos of uncoated and SUSC coated glass; b) is the photo of the sliding marked water (30 μL) and n-dodecane (30 μL) droplets on SUSC; c) is the photo of the sliding marked water droplet (30 μL) on PDMS; d) is the photo of the sliding marked water droplet (30 μL) on PVDF;

[0031] Figure 3In the figure, a) is a high-speed camera image of water droplets on the surface of SUSC; b) is the surface free energy of uncoated glass, PDMS and SUSC; c) is the sliding angle and contact angle hysteresis of the uncoated glass, PDMS and SUSC surfaces; d) is a schematic diagram of droplet sliding on the surfaces of uncoated glass, PDMS and SUSC; e)-g) are characterization diagrams of the effect of hot steam on the formation of droplet aggregates on uncoated copper sheets; h)-j) are characterization diagrams of high-temperature steam and condensed water droplets on SUSC coated copper plates;

[0032] Figure 4 a) Schematic diagram of contaminants of different sizes from nanometers to centimeters; b) and f) are SEM images of TiO2 nanoparticles (≈20nm) residues on uncoated glass and SUSC; c) and g) are SEM images of TiO2 nanoparticles residues on uncoated glass and SUSC; d) and h) are SEM images of SiO2 nanoparticles (≈1μm) residues on uncoated glass and SUSC; e) and i) are comparisons of contamination between uncoated glass and SUSC containing gravel (≈200μm) before and after rinsing with water droplets (tilt angle ≈10°);

[0033] Figure 5 a) is the infrared thermal imaging image and cooling time comparison diagram of PU and SUSC from about 60°C to 50°C; b) is the cooling diagram of PU and SUSC at room temperature; c) is the temperature change diagram of PU and SUSC in the cycle test (heating to the same temperature and then cooling at room temperature);

[0034] Figure 6 In the figure, a) is a working principle diagram of a SUSC-coated LED lamp in a NaCl solution; b) is a working state of an LED bulb without and with SUSC in a NaCl solution; c) is a working state diagram of a circuit board after SUSC is coated in a NaCl solution; d) is a SEM cross-sectional view of a SUSC-coated copper wire;

[0035] Figure 7 This is a comparison chart of the coatings prepared in Example 2 of the present invention, Comparative Example 1 and Comparative Example 2 being cured on a metal substrate at room temperature. DETAILED DESCRIPTION

[0036] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0037] The present invention will be further described below in conjunction with the embodiments.

[0038] Material

[0039] Perfluorodecyl acrylate (PFDA) and isobornyl acrylate (IBOA) were purchased from McLean Biochemical Technology Co., Ltd. (Shanghai).

[0040] Azobisisobutyronitrile (AIBN) was provided by Aladdin Biochemical Technology Co., Ltd. (Shanghai).

[0041] Anhydrous ethanol was purchased from Sinopharm Chemical Reagent Co., Ltd., and polydimethylsiloxane (PDMS) was purchased from Shenzhen Hongyejie Technology Co., Ltd.

[0042] Perfluoro-1,2-dimethylcyclohexane and hexafluoropropylene dimer were supplied by Guochen Taifu Co., Ltd. (Jinan).

[0043] PU was purchased from China Daoguan Co., Ltd.

[0044] Polyvinylidene fluoride (PVDF) was provided by Zhongcheng Plastic Co., Ltd. (Jieyang, China).

[0045] All chemicals were of analytical grade and used without further purification.

[0046] Example 1

[0047] Preparation of solid smooth coating

[0048] Perfluoro 1,2-dimethylcyclohexane (7 mL) and hexafluoropropylene dimer (3 mL) were added to a 100 mL round-bottom flask and stirred magnetically. After stirring at room temperature for 30 minutes, perfluorodecyl acrylate (0.03 g) and isobornyl acrylate (0.02 g) were added to the mixture. The mixture was stirred at room temperature for 15 minutes. 0.01 g of azobisisobutyronitrile AIBN was dropped into the mixture to crosslink and polymerize perfluorodecyl acrylate with isobornyl acrylate at 60 ° C for 2 hours. After the reaction, the resulting suspension was spin-coated on a substrate and then rapidly cured at room temperature (25 ° C) to form an ultra-slippery pure solid surface.

[0049] SUSC coating surface morphology

[0050] The morphology of the SUSC coating surface was observed by scanning electron microscopy. The element distribution was scanned on a field emission scanning electron microscope (SUPRA TM, 55Zeiss, Germany). After SUSC was sprayed on the glass substrate and solidified, it was quenched with liquid nitrogen. Each sample was cleaned with nitrogen before testing, and then gold was sprayed on the sample surface. The test temperature was 25°C, and the AFM measurement was performed on a Dimension atomic force microscope (ICON2-SYS, Bruker, USA).

[0051] Structural characterization of SUSC

[0052] The prepared SUSC emulsions were characterized by FTIR and XPS. Fourier transform infrared (FTIR) spectra were collected on a spectrometer (Nicolet IS20, Thermo Fisher Scientific Inc., Waltham, MA, USA) with a scanning range of 4000–400 cm –1 , the scanning speed was 2 mm / s. X-ray photoelectron spectroscopy (XPS) was performed on a monochromatic al-k-α source k-α photoelectron spectrometer (ESCALAB, Beijing, China).

[0053] Measurement of light transmittance of SUSC coating surface

[0054] The transmittance of USC-coated surfaces was measured on a UV-visible spectrophotometer (UV-2600, Shimadzu, Japan). SUSC was sprayed on a glass slide (7.5 cm × 2.5 cm), while the original glass slide was used as a control. The transmittance of air was set as the baseline for the test. The test wavelength range was 400 nm to 2500 nm.

[0055] Surface wettability test

[0056] The contact angle and sliding angle were measured on a dynamic / static optical contact angiometer (SL250, KINO, USA). SUSC was coated on a 7.5 cm × 2.5 cm glass slide, and the liquid volume was 10 μL each time. After the droplet stabilized, a side view image was taken with a camera. For the measurement of the sliding angle, a motor-controlled rotatable test platform was used to change the surface angle, and the rotation angle was fed back to the computer in real time. The sliding angle (θr) is the tilt angle of the surface when a droplet of a certain volume (10 μL) is about to roll on the inclined surface. When the liquid (10 μL) rolls on the solid surface, due to the energy barrier at the interface in front of the droplet, there is an unequal contact angle before the droplet (θa) and after (θr), which is called the hysteresis contact angle (H). θ ).

[0057] Measurement of surface energy

[0058] The surface energy (SE) of the different coatings was calculated using the Owens-Wendt-Rabel-Kaeble (OWRK) method with DI water and methane disulfide on a CAM 200 optical contact angle goniometer (KSV Instruments Co., Ltd., Helsinki, Finland) at 25°C.

[0059] Surface lubricity test

[0060] The surface lubrication performance was characterized by testing the sliding speed of a water drop on the inclined coating surface (8°). A video of a water drop sliding from the inclined coating surface was obtained on a digital camera (Sony, FDR-AX60, Japan). The sliding time of the drop from the starting point to the bottom of the slope was tested by a timer and video editing software (Pr). The sliding speed of the drop was calculated based on the length of the slope path. The average value was taken as the sliding speed of the drop.

[0061] Surface temperature test

[0062] The samples coated on the paulownia wood board with an area of ​​5 cm × 5 cm were placed on the vacuum insulation board above the ground (0.7 m) to prevent heat conduction from the ground. Temperature measurements were performed using a thermocouple data logger (testo 176). Thermal measurements of a blank copper plate were also performed under the same test conditions for comparison. Infrared images of the SUSC were obtained by continuous shooting on a handheld thermal infrared imager (ut160h unit-t, Shenzhen, China) at a fixed distance.

[0063] Results and Discussion

[0064] SUSC composition and coating surface

[0065] A typical solid smooth surface was prepared with high light transmittance close to glass (close to 100%). Figure 1 a shows the flat and smooth surface of the coated SUSC. Even after magnification, it is very uniform and smooth (Figure S2a). EDS results show that the carbon-oxygen-fluorine elements are evenly distributed on its surface ( Figure 1 b, S2b, c), which is necessary for the anti-slip properties of the SUSC surface. An ultra-thin coating with a thickness of about 1.5 μm was obtained by a common spraying method ( Figure 1 c). Ultra-thin structures are more conducive to its optical transparency and heat dissipation. In addition, SUSC coatings can be successfully fabricated on almost all types of water-insoluble substrates, such as glass, silicon, ceramics, metals, plastics, etc. In addition, it is also suitable for coating electronic components. Using AFM to observe the rough structure of the SUSC surface, such as Figure 1 As shown in middle (d), almost no change in roughness was found. The low RMS (1.76 nm) of the SUSC surface further confirmed its low surface roughness at the nanoscale without aggregation.

[0066] To further investigate the composition of SUSC, the FTIR spectra of PFDA and the final polymerization product were as follows Figure 1 f and Figure S1. 1410cm -1 The peak at 1730 cm-1 (CH deformation peak of vinyl β-carbon) disappears. -1(carbonyl stretching peak) and 810cm -1 The intensity of the unsaturated olefin bending vibration peak weakened, confirming that the monomers were polymerized to form SUSC. In addition, no C=C bonds were found in SUSC, indicating that the acrylic monomers were fully reacted. These results also confirmed that SUSC has a low surface energy ( Figure 1 g, h, i). The high atomic ratio between fluorine and oxygen indicates that the perfluoroalkyl side groups are significantly enriched on the coating surface. Previous studies have shown that perfluoroalkyl side chains containing more than 8 -CF2 units show a clear tendency to crystallize in a highly ordered liquid crystal smectic B phase. In this case, the terminal -CF3 groups are arranged in a uniform hexagonal pattern on the SUSC surface ( Figure 1 , g inserted). This structural feature is beneficial to minimize the surface free energy and shield the electrical effect of polar groups. Therefore, the low interaction between the surface and different contact liquids leads to a completely hydrophobic and smooth surface with self-cleaning properties.

[0067] SUSC's transparency and self-cleaning properties

[0068] The light transmittance of SUSC was tested and compared with that of uncoated glass. Figure 2 As shown in Figure a, in the wavelength range of 400 to 2500 nm, the transmittance curves of SUSC-coated glass and uncoated glass completely overlap. In addition, the sprayed SUSC can still be seen on the 5×5 cm glass substrate. The optical photograph of the SUSC coating on a large-sized glass substrate (5cm×5cm) shows that the coating can be scaled up without affecting its transparency.

[0069] Figure 2 Figures a, b, c, and d show that water and oil droplets (n-dodecane) can be easily removed from the SUSC coated glass surface without leaving any residual film. The water and oil droplets were observed to slide off the surface at an angle of 12° in about 1.5 s without any trace. SUSC was compared with two other typical low surface energy materials, polydimethylsiloxane (PDMS) and polyvinylidene fluoride (PVDF). Water could not slide along the PDMS and PVDF surfaces, even though PDMS and PVDF are considered to be widely used hydrophobic materials.

[0070] These results confirm that the SUSC coating has an excellent fully hydrophobic smooth surface with excellent self-cleaning properties against water and oil contamination. In terms of water contamination resistance, the SUSC coating exhibits similar properties to superhydrophobic surfaces, but its water sliding angle is higher than that of superhydrophobic surfaces.

[0071] SUSC surface wettability

[0072] In order to observe the movement trajectory of the water droplet on the top of the SUSC, a high-speed camera with a frame rate of 7400fps was used to capture the movement dynamics of the water droplet. When the water droplet contacted the SUSC surface at an 8° tilt angle, the water droplet began to slide and spread. At 20ms, a pancake shape with a maximum diffusion diameter was formed, which is similar to the bounce of the droplet on the surface of the super-hydrophobic coating. The droplet continued to move forward for about 1 cm (0.17 in) in 360 milliseconds. Figure 3 (a)

[0073] The surface energies of SUSC coating, PDMS, and uncoated glass were also tested. Fluorine enrichment on the SUSC surface exhibited lower surface energy compared to uncoated glass and PDMS. Low hysteresis contact angle (HCA:H) and sliding angle (SA:θr) ( Figure 3 b, c), resulting in a dynamically smooth liquid surface with low SE, low surface roughness, and good uniformity. Therefore, the contact angles Hpe and θr of SUSC are only 10°, which are much lower than those of PDMS (contact angles Hpe and θr ≈ 70°) ( Figure 3 (d)

[0074] In addition, a high temperature steam resistance test was conducted. During the high temperature steam fumigation process, ordinary copper was covered with condensation of water droplets ( Figure 3 h,i,j), but on the SUSC-coated copper sheet, the water mist condensed into water droplets and slid down within 3 seconds. After 6 seconds, most of the copper sheet surface was cleaned ( Figure 3 (e, f, g). High-temperature steam shock resistance tests show that the SUSC coating maintains its surface integrity and has good anti-slip properties even under continuous high-temperature steam shock. Evaporated water molecules gradually condense into droplets after contacting the SUSC surface. These droplets then merge and detach from the surface. In contrast, the same phenomenon is not found on smooth copper sheets.

[0075] Self-cleaning properties of SUSC coatings

[0076] Smooth surfaces are widely used to prevent contamination because the coating shields potential contaminant contact. In addition, contaminants can easily remain on smooth surfaces with low affinity under the drive of external forces. Therefore, the anti-adhesion properties of SUSCs were tested using selected contaminants, including TiO2 nanoparticles (~20 or 200 nm), SiO2 nanoparticles (~1 μm), and gravel particles (~200 μm). Figure 4 a). TiO2 nanoparticles and SiO2 microparticles of different sizes (2 mL) were dropped onto uncoated glass and SUSC at a 45° angle. The surface contaminants were observed using a scanning electron microscope. There was almost no contaminant left on the SUSC without water washing ( Figure 4 Further statistics of residual pollutants on the surface of SUSC confirmed the self-cleaning ability of SUSC ( Figure 4 f, g, h insets). The element fractions before and after contamination show that no contamination elements were found on the SUSC coated surface. However, a large amount of residue was present on the uncoated glass ( Figure 4 a, b, c, d and inset).

[0077] The above results show that the smoothness of SUSC can resist micron- and nano-scale contaminants. The sand (200 μm) laid on the ordinary glass and the coated glass was washed with water at an inclination angle of 10°. The sand on the SUSC can be easily washed away by water ( Figure 4 i), while the uncoated glass retained a lot of grit ( Figure 4 e). This proves that a large number of pollutants can be easily removed without any residue.

[0078] Thermal properties of SUSC coatings

[0079] In order to understand the heat transfer performance of the SUSC coating, the temperature distribution of the coating was recorded when it was heated by a heat source at the bottom. Figure 5 As shown in a, the temperature distribution of the SUSC coating (thickness of about 1.5 μm) within a 3-min interval is uniform. However, due to the poor thermal conductivity of the PU layer, it takes 183 seconds for the temperature of the copper sheet to drop by 10°C. Using PU coating as a radiation cooling layer in electronic devices may cause local high temperatures to rise, resulting in damage to the electronic equipment. The results show that the center temperature of the sample only drops from the initial 60°C to 50°C after 3 minutes, indicating that the thermal conductivity of the PU coating is poor. The SUSC coating can significantly reduce the coating temperature from 60°C to 50°C, a decrease of 10°C, which is due to the thermal radiation characteristics of SUSC.

[0080] The temperature distribution of the SUSC coating is significantly more uniform. It took only 146 seconds for the temperature to drop from the initial 60°C to 50°C. Compared with the PU coating, the temperature uniformity and heat dissipation of the SUSC coating are improved. Figure 5 As shown in (b), the cooling rate of the SUSC-coated copper sheet is significantly slower than that of the PU-coated copper sheet. In addition, the durability of the SUSC coating was evaluated by a temperature cycle test (heating to the same temperature and then cooling at room temperature). Figure 5 c. After 13 cycles, the SUSC coating exhibits good cooling performance.

[0081] The most important feature of SUSC coatings is that they form an ultra-thin coating on the substrate. This makes them the best candidate for waterproof packaging of small precision electronic devices. The coating effectively protects electronic components from contamination by water, oil and other contaminants while maintaining the functionality of the electronic devices under different operating conditions. Figure 6 a is the working principle diagram of SUSC coated LED lamp in NaCl solution. Figure 6 As shown in Figure b, the LED lamp is connected to the battery with a wire and placed in a NaCl solution (1 mol / L). The uncoated bulb does not work in the NaCl solution due to a short circuit in the wires. In contrast, the SUSC coating can ensure that the LED lamp works in the NaCl solution. Figure 6 As can be seen from the figure, the copper wire is protected by the outer layer of the SUSC coating, which further verifies the good waterproof performance of SUSC. Larger areas and complex electronic devices can be coated by the spraying method. Figure 6 As shown in Figure c, after applying SUSC coating on the circuit board, the electronic light can work in water, and the ultra-thin SUSC coating does not increase the thickness or weight of the electronic components.

[0082] Example 2

[0083] Preparation of solid smooth coating

[0084] Perfluoro 1,2-dimethylcyclohexane (8 mL) and hexafluoropropylene dimer (3 mL) were added to a 100 mL round-bottom flask and stirred magnetically. After stirring at room temperature for 30 minutes, perfluorodecyl acrylate (0.05 g) and isobornyl acrylate (0.04 g) were added to the mixture. The mixture was stirred at room temperature for 15 minutes. 0.02 g of azobisisobutyronitrile AIBN was dropped into the mixture to crosslink and polymerize perfluorodecyl acrylate with isobornyl acrylate at 63 ° C for 1.8 h. After the reaction, 5 mL of the obtained suspension was spin-coated on a metal substrate, and then rapidly cured at room temperature for 60 s to form an ultra-smooth pure solid surface.

[0085] The prepared suspension was dropped onto a metal substrate and then rapidly solidified at room temperature within 60 s. Figure 7 shown.

[0086] Example 3

[0087] Preparation of solid smooth coating

[0088] Perfluoro 1,2-dimethylcyclohexane (7 mL) and hexafluoropropylene dimer (3 mL) were added to a 100 mL round-bottom flask and stirred magnetically. After stirring at room temperature for 30 minutes, perfluorodecyl acrylate (0.02 g) and isobornyl acrylate (0.03 g) were added to the mixture. The mixture was stirred at room temperature for 15 minutes. 0.01 g of azobisisobutyronitrile AIBN was dropped into the mixture to crosslink and polymerize perfluorodecyl acrylate with isobornyl acrylate at 65 ° C for 2 hours. After the reaction, 5 mL of the obtained suspension was spin-coated on a metal substrate, and then rapidly cured at room temperature for 65 seconds to form an ultra-smooth pure solid surface.

[0089] Comparative Example 1

[0090] The difference from Example 2 is that perfluoro-1,2-dimethylcyclohexane (7 mL) and hexafluoropropylene dimer (3 mL) are replaced with 11 mL of ethanol, and the rest are the same as Example 2.

[0091] After a drop of the prepared coating is dropped on a metal substrate, the coating is difficult to cure at room temperature. Figure 7 As shown, the applied coating is still not cured after 20 minutes at room temperature.

[0092] Comparative Example 2

[0093] The difference from Example 2 is that perfluoro-1,2-dimethylcyclohexane (7 mL) and hexafluoropropylene dimer (3 mL) are replaced with 11 mL of ethyl acetate, and the rest are the same as Example 2.

[0094] After a drop of the prepared coating is dropped on a metal substrate, the coating is difficult to cure at room temperature. Figure 7 As shown, the applied coating is still not cured after 20 minutes at room temperature.

[0095] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a self-cleaning, waterproof and heat-dissipating coating, characterized in that: The steps include: Mix perfluoro-1,2-dimethylcyclohexane and hexafluoropropylene dimer at 20-35°C; After the reaction is completed, perfluorodecyl acrylate and isobornyl acrylate are added to the mixture, and the mixture is stirred at 20-35° C. for reaction; After stirring, AIBN is added to the reaction system and heated to allow perfluorodecyl acrylate and isobornyl acrylate to cross-link and polymerize for a set time to obtain a coating.

2. The method for preparing the self-cleaning, waterproof and heat dissipating coating according to claim 1, characterized in that: The mass ratio of perfluoro 1,2-dimethylcyclohexane, hexafluoropropylene dimer, perfluorodecyl acrylate and isobornyl acrylate is 10-15:4-6:0.01-0.05:0.01-0.

05.

3. The method for preparing the self-cleaning, waterproof and heat dissipating coating according to claim 2, characterized in that: The mass ratio of perfluoro 1,2-dimethylcyclohexane, hexafluoropropylene dimer and perfluorodecyl acrylate is 10-13: 4-10: 0.02-0.04: 0.02-0.

04.

4. The method for preparing the self-cleaning, waterproof and heat dissipating coating according to claim 2, characterized in that: The mass ratio of perfluorodecyl acrylate to AIBN is 2-4:

1.

5. The method for preparing the self-cleaning, waterproof and heat dissipating coating according to claim 1, characterized in that: The perfluoro-1,2-dimethylcyclohexane and hexafluoropropylene dimer are stirred and reacted at 20-35° C. for 20-40 minutes.

6. The method for preparing the self-cleaning, waterproof and heat dissipating coating according to claim 1, characterized in that: After adding perfluorodecyl acrylate and isobornyl acrylate to the mixture, the stirring time is 10-30 minutes.

7. The method for preparing the self-cleaning, waterproof and heat dissipating coating according to claim 1, characterized in that: The temperature for cross-linking polymerization of perfluorodecyl acrylate and isobornyl acrylate is 55-65° C. and the time is 1.5-2.5 hours.

8. A self-cleaning, waterproof, heat-dissipating coating, characterized in that: Prepared by the preparation method described in any one of claims 1 to 7.

9. Use of the self-cleaning, waterproof and heat-dissipating coating according to claim 8 in coating and packaging electronic devices.

10. The use according to claim 9, characterized in that: When coating and packaging electronic devices, the coating is dripped on or coated on the surface of the electronic devices and cured at 20-35°C.

Citation Information

Patent Citations

  • Fluorescent visible fluorine-silicon electronic protective coating and preparation method thereof

    CN111534186A

  • Fluorine-containing methacrylate polymer, self-cleaning coating, preparation method and application

    CN113773437A

  • Flexible transparent super-hydrophobic polymer as well as preparation and application thereof

    CN115819664A